The project management answer book - Furman, Jeff (Management Concepts Press, 2015)
With a new chapter on Scrum agile, updates throughout, and many additional PMP test tips, this new edition builds on the solid foundation of the first edition. The structure of this update maps closely to the PMBOK guide V5 and is designed to assist anyone studying for the PMP and other certification exams. Helpful sections cover: networking and social media tips for PMs, including the best professional organizations, virtual groups, and podcast resources; formulas PMs need to know, plus a template to help certification candidates prepare and self-test for their exams; quick study sheet for the processes covered on the PMP exam; key changes in PMBOK guide V5, for readers familiar with earlier versions who want the skinny on the new version. --